Gambaran Pengetahuan Pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Panti Rapih Yogyakarta - Dita Hanna Febriani; Relinda Putri, Tektista; Noor Hidayah, Fadila Rahma (I Care Jurnal Keperawatan STIKes Panti Rapih, 2025)
Background: The variety level of type 2 diabetes mellitus patients’ knowledge about the disease and its management can affect blood glucose levels. Good knowledge of diabetes is essential to control blood sugar and improving the quality of life of patients. Conversely, low knowledge can hinder disease management and cause complications. Objective: To determine the knowledge in type 2 DM patients at the Endocrine Clinic of Panti Rapih Hospital Yogyakarta. Method: This research is a descriptive quantitative study with a cross-sectional design. The respondents in this study were 96 samples selected by purposive sampling technique. Diabetes Knowledge Questionnaire (DKQ-24) used to collect the data. Results: More than half of the respondents in this study were classified as elderly, female, unemployed, diagnosed with type 2 DM for ≥ 5 years, had disease complications, and less than half of the respondents had higher education, namely bachelor's degrees. Most respondents had received information related to type 2 DM, information obtained from health workers, and more than half of the information provided was related to management. The majority of respondents with type 2 DM had moderate level of knowledge. Conclusion: Nurses need to be more active in providing DM education, especially in etiology and complications.